The Role Of Gut Microbiota, Firmicutes/Bacteroidetes Ratio, And Short Chain Fatty Acids In The Pathogenesis Of Type 2 Diabetes Mellitus - Ade Dharmawan; Nicolas Layanto; Monica Cherlady Anastasia (Universitas Pahlawan Tuanku Tambusai, 2026)
AbstractThis study aims to understand the role of gut microbiota imbalance, specifically an increased ratio of Firmicutes to Bacteroidetes, in the pathogenesis of type 2 diabetes mellitus (T2DM). Using systematic literature review and thematic analysis. Data were collected from various scientific sources, including journal articles indexed in PubMed, Scopus, and ScienceDirect, this study explores how gut dysbiosis contributes to insulin resistance, impaired glucose metabolism, and chronic inflammation. The results show that changes in microbiota composition result in increased energy extraction from food, impaired gut barrier integrity, and altered production of short-chain fatty acids (SCFAs) such as butyrate, which play a role in glucose homeostasis and inflammation regulation. These findings also emphasize the potential of probiotic, prebiotic, and dietary modification interventions to restore microbiota balance, improve insulin sensitivity, and reduce oxidative stress. Overall, this study highlights the urgency of a personalized approach in the management of T2DM through modulation of the gut microbiota based on the latest clinical and mechanistic evidence.